Landscaping Methods to Prevent Pests from Entering Your Home: ENY2098/IN1397, 3/2023 - Davis, J. E.; Oi, F.; Sanderson, L.; Moffis, B.; Lester, B. (EDIS, 2023)
Pests can damage your home and harm your health. Two important ways to reduce pest entry into your home are frequent inspections and proper landscaping practices. To ensure complete success, Integrated Pest Management (IPM) program must be implemented. IPM resources for common landscape pests are provided at the end of this publication for further information and convenience. This publication is intended for homeowners, Extension professionals, and anyone interested in preventing pests from entering the built environment.